Getting the Court in Your Business: Unmarried Parents, Institutional Intersectionality, and Establishing Parenting Time Orders in Family Court. (26th August 2019) - Waller, Maureen R
Abstract: The child support program reaches half of poor children in the United States, and recent policy proposals would incorporate parenting time into all initial child support orders. Despite the importance and scope of these proposed changes for unmarried parents, research about how parents interpret the decision to set up parenting time orders in family court is limited. Qualitative evidence from individual and group interviews shows that unmarried mothers and fathers perceive family court through competing frames, leading to strategies of either avoidance or engagement with the court system in certain circumstances. Some parents in the study framed family courts as intrusive and opted to stay away from court to avoid unwanted scrutiny by the child welfare and criminal justice systems. In contrast, other parents framed family courts as protective of their families and sought legal help when their child's custody was ambiguous, their child's safety was threatened, or their status in public programs was at stake. These findings are consistent with research on institutional distrust and avoidance but also suggest heterogeneity in unmarried parents' views of family court as a system that both surveils and safeguards poor families. Findings further demonstrate that unmarried parents view these decisions from a position of institutional intersectionality, or their position at the intersection of multiple state systems that interact with the courts.